FACTORS INFLUENCING CAPITAL STRUCTURE WITH PROFITABILITY AS A MODERATOR - Halim, Kusuma Indawati; Novianty, Novianty (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
A company's capital structure is an important element in ensuring the smooth running of its business activities. Management is required to decide the ideal capital structure by considering the subsidizing needs of both internal and external funding productively. The research goal is to discover how business risk and firm size affect the capital structure that is moderated through profitability. The study pattern consisted of 37 companies in the property and real estate sector, which have been decided on through a purposive sampling method. The test results show that business risk has a negative effect on a company's capital structure, and firm size has no effect on this. Furthermore, profitability also has a moderating effect on the negative relationship between business risk and capital structure, as well as the positive relationship between firm size and capital structure.